2020
DOI: 10.4081/ija.2020.1754
|View full text |Cite
|
Sign up to set email alerts
|

First insight of exogenous addition of proline and glycinebetaine to mitigate fluorine toxicity effects on common bean seedlings

Abstract: To counteract fluoride (F) stress-induced adverse effects on plants, one approach is the application of exogenous potential osmoprotectants such as proline (Pro) and glycinebetaine (GB). This experiment was carried out to evaluate the effects of exogenous application of Pro and GB on germination and growth of common bean seeds after potassium fluoride (KF) and sodium fluoride (NaF) exposure. The study was replicated under two different temperatures: the normal temperature required for seeds growth (20°C) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…In this study, partial inhibition of germination was observed in African bean genotypes under KF200, while a stronger effect was observed under NaF200 where even germination was completely inhibited. Similar results describing a more toxic effect of NaF than KF on bean growth were reported by Chahine et al (2021). The higher toxicity of NaF than KF could be explained by a possible synergistic effect of Na and F together causing the inhibition of vital systems in plants.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, partial inhibition of germination was observed in African bean genotypes under KF200, while a stronger effect was observed under NaF200 where even germination was completely inhibited. Similar results describing a more toxic effect of NaF than KF on bean growth were reported by Chahine et al (2021). The higher toxicity of NaF than KF could be explained by a possible synergistic effect of Na and F together causing the inhibition of vital systems in plants.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, partial inhibition of germination was observed in African bean genotypes under KF200, while a stronger effect was observed under NaF200 where even germination was completely inhibited. Similar results about a more toxic effect of NaF than KF on bean growth have been reported by Chahine et al (2021). The higher toxicity of NaF than KF could be justi ed by a possible synergistic effect of Na and F together causing the inhibition of vital systems in plants.…”
Section: Discussionsupporting
confidence: 83%